TINGKAT AKTIVITAS FISIK PESERTA DIDIK KELAS ATAS SD NEGERI 2 TONATAN KABUPATEN PONOROGO - Pratama, Teddy Giolanda; Ellan Ziqra (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2025)
The purpose of this study is to determine the level of physical activity among upper-grade students at SD Negeri 2 Tonatan, Ponorogo Regency. Physical activity involves movements of the body that require energy, and for individuals, maintaining physical and mental condition is crucial to sustain a good quality of life throughout the day. This research is a quantitative descriptive study conducted at SD Negeri 2 Tonatan, Ponorogo Regency, East Java Province. The method employed is a survey method using the Physical Activity Questionnaire for Children (PAQ-C) as the instrument. The subjects in this study are all upper-grade students at SD Negeri 2 Tonatan, totaling 116 students. The data analysis technique utilized is quantitative descriptive analysis using percentages.The results of the study indicate that the level of physical activity among upper-grade students at SD Negeri 2 Tonatan, Ponorogo Regency, is as follows: very low category, 2 students or 1.7%; low category, 41 students or 35.3%; moderate category, 38 students or 32.8%; high category, 26 students or 22.4%; and very high category, 9 students or 7.8% of the total number of upper-grade students. The data obtained shows that the majority of upper-grade students at SD Negeri 2 Tonatan, Ponorogo Regency, have a low level of physical activity.